Antibacterial Potential of Vatica diospyroides Flower Extracts: Targeting Diverse Pathogens in Aquaculture - Juthatip Yooklaen; Theera Srisawat; Luu Tang Phuc Khang; Nguyen Dinh-Hung; Papungkorn Sangsawad; Nguyen Vu Linh; Patima Permpoonpattana (International Journal of Microbiology, 2025)
Vatica diospyroides, an endemic species of the Dipterocarpaceae family, possesses notable medicinal properties. However, its application as an antibacterial agent is limited due to the insufficient investigations of its antibacterial activity from flower extracts. This study is aimed at exploring the antibacterial mechanisms of acetone extracts from the flowers of V. diospyroides against four bacterial strains using various methods, including the well-disk diffusion assay, minimum inhibitory concentration (MIC) determination, minimum bactericidal concentration (MBC) assessment, flow cytometry, and scanning electron microscopy. The inhibition zones measured between 6.33 and 17.66 mm. Notably, the extract exhibited different MIC values, such as 250 μg mL-1 for Bacillus subtilis and Escherichia coli, and only 62.5 μg.mL-1 for Vibrio parahaemolyticus, demonstrating its effectiveness. MBC values ranged from 500 to over 1000 μg mL-1 for Pseudomonas aeruginosa. Flow cytometric analysis revealed that the cellular responses to the extract were influenced by both the concentration of the extract and the duration of exposure, indicating a dose- and time-dependent antibacterial effect. Additionally, scanning electron microscopy confirmed that the extract caused structural damage to the cells of both Gram-positive and Gram-negative bacteria. Overall, this study underscores the promising antibacterial potential of V. diospyroides flower extracts, which demonstrate significant efficacy against a variety of bacterial strains.